Determinants of Intellectual Capital on Financial and Market Performance: The Moderating Role of Board Function - Marbun , Daniel Ranbon Bungaran; Ulpah, Maria (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to specifically examine the impact of intellectual capital on financial and market performance, considering the moderating role of board function. The study uses a sample of non-financial companies listed on the Indonesia Stock Exchange over the period 2017-2022. The approach employed in this research is panel regression to test the relationships between variables. The results indicate that intellectual capital has a significant effect on return on assets (ROA). Additionally, the role of the board function strengthens the impact of intellectual capital on return on assets as a moderating variable. The implications of this study suggest that company management should consider increasing investment in the development and utilization of intellectual capital. This can include employee training and development, effective knowledge management, and innovation development, which can ultimately enhance the overall value of the company.